SOCIODEMOGRAPHIC PROFILE OF YOUNG PEOPLE AND THEIR LEISURE NEEDS IN THE CITY OF NOVO HAMBURGO/RS/BRAZIL (Fiep Bulletin - online, 2013)
The objective of this study was to diagnose sport and leisure activities offered to youth by public authorities in the Brazilian city of Novo Hamburgo, RS. This was a quantitative, descriptive study of a sample of 60 young people from Novo Hamburgo. A questionnaire containing both open and closed questions was administered during the first half of 2010 in a number of different neighborhoods in Novo Hamburgo, RS. The main results were as follows. Ninety-two percent (92%) of the young people questioned reported that if they were given the opportunity to take part in some type of physical activity/sport they would be in favor of doing so, but 8% had no interest in engaging in physical activity. It was notable that more than 70% of the sample of young people were interested in group sports. We should also emphasize the finding that the locations for practicing physical activity listed by the young people illustrated the weakness of public facilities, since the great majority of locations mentioned were private. The respondents reported that one reason why they didn't engage in these activities was a lack of free time and that factors that could encourage them to do so would be better infrastructure and more accessible locations. As a result of these complaints, we found that 51.7% of these young people were unaware of the existence of leisure equipment in the city, while 45% believed that leisure equipment was available. The young people's main concerns relating to the locations where they engage in activity were adequate safety and whether or not the infrastructure and materials (6.6%) available were appropriate and in good working order. We conclude that despite having to balance work, study and leisure, our young people still try to engage in physical or sporting activities, using their free time in the best manner possible. Even though the city investigated here has a policy for sport and leisure focused on the youth age group, it does not cover all young people, being restricted to a small proportion of them who are considered socially vulnerable.
Keywords: youth; young people; sport/leisure; public policies